Uji Aktivitas Sitotoksik Ekstrak Daun Matoa (Pometia pinnata) dengan Metode BSLT (Brine Shrimp Lethality Test) - Rahmawati, Junita Eka; Wati, Aulia; Handayani, Selpida (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Matoa plant (Pometia pinnata) is a typical Papuan plant included in the Sapindaceae family which can relieve hypertension and has diuretic, antidiabetic and antioxidant activities. Matoa leaves contain chemical alkaloids, flavonoids, saponins, and steroids. The purpose of this study was to determine the toxic effect and LC50 value of n-hexan extract of matoa leaves against Artemia Salina Leach larvae. Extraction is carried out by maceration method with n-hexane solvent. The n-hexan extract of matoa leaves is prepared in a test solution with concentration variations of 500 ppm, 750 ppm, 1000 ppm, and 1500 ppm. Toxicity testing was carried out using Artemia Salina Leach larvae then the toxic effect of the extract was identified with the percentage of death of Artemia Salina Leach larvae using probit analysis (LC50). The results of this study showed the highest mortality at a concentration of 1500 ppm with the death of 30 larvae. Based on the results of the research conducted, it can be concluded that matoa leaf extract (Pometia pinnata) has a toxic effect on Artemia Salina Leach larvae with a Lethal Concentration value of 50 (LC50) of 509.577 ppm and is included in the toxic category.